Cloud computing to automate information units - Fernández Morales, Mynor (2012)
This article will address the main technical aspects that facilitate the use and growth of cloud computing technologies, which go hand in hand with the emergence of more and better Internet services and the technological development of broadband. Finally, the impact of cloud computing technologies on the automation of information units will be discussed.